Blogging developer knowledge: Motivations, challenges, and future directions - PARNIN, Chris (Institutional Knowledge at Singapore Management University, 2013)
Why do software developers place so much effort into writing public blog posts about their knowledge, experiences, and opinions on software development? What are the benefits, problems, and tools needed-what can the research community do to help? In this paper, we describe a research agenda aimed at understanding the motivations and issues of software development blogging. We interviewed developers as well as mined and analyzed their blog posts. For this initial study, we selected developers from various backgrounds: IDE plugin development, mobile development, and web development. We found that developers used blogging for a variety of functions such as documentation, technology discussion, and announcing progress. They were motivated by a variety of reasons such as personal branding, knowledge retention, and feedback. Among the challenges for blog authors identified in our initial study, we found primitive tool support, difficulty recreating and recalling recent development experiences, and management of blog comments. Finally, many developers expressed that the motivations and benefits they received for blogging in public did not directly translate to corporate settings.